IMAGE FORMING APPARATUS - FUKUI AKITOMO (2021)
To solve the problem in which an image forming apparatus with multiple antennas for detecting a direction of arrival of a radio wave has not been devised in the past.SOLUTION: A communication substrate having a plurality of antennas for wireless communication with a communication terminal is provided at a position protruding from a top surface of the image forming apparatus in the vertical direction of the image forming apparatus, and where the plurality of antennas does not overlap with any member when the image forming apparatus is viewed from the front side.SELECTED DRAWING: Figure 2 【課題】 従来、電波の到来方向を検出するための複数のアンテナを有する画像形成装置は考案されていなかった。【解決手段】 通信端末と無線通信を行うためのアンテナを複数有する通信基板を、前記画像形成装置の鉛直方向において前記画像形成装置の上面から突出した位置であり、前記画像形成装置を正面から見た場合に前記複数のアンテナがいずれの部材とも重ならない位置に設ける。【選択図】 図２